Intraperitoneal administration of NK-92 improves survival in xenografts of early and established ovarian cancer models - Paula Marcus; Jenny Warrington; Michael Zhang; Manjunatha Ankathatti-Munegowda; Xing-Hua Wang; Iran Rashedi; Armand Keating (PLoS ONE, 2026)
Ovarian cancer (OC) is a leading cause of gynecological cancer-related mortality. Management remains challenging as the disease frequently presents with intra-abdominal metastases at diagnosis, standard therapies can be associated with severe complications and disease recurrence is common. While cellular immunotherapy is increasingly investigated as a promising approach, the most effective routes of administration need to be established. We have investigated NK cell therapeutics as a less toxic option and examined the permanent NK cell line, NK-92, as a suitable model. Here, we report two xenograft mouse models with the ovarian adenocarcinoma cell line, SKOV-3, representing early-stage OC and late-stage OC with ascites to comprehensively evaluate the anti-cancer efficacy of different routes of NK-92 administration. Bioluminescence imaging, cell tracking with the IVIS system and animal survival were used to evaluate outcomes. The cells were administered via intraperitoneal (IP), intravenous (IV), or a combination of IP and IV routes. We showed that NK-92 significantly increased animal survival when delivered IP ( p = 0.009 and p = 0.018) or combined IP and IV ( p = 0.05 and p = 0.017) in early and established OC xenografts, respectively, whereas intravenous delivery at similar doses had no effect on survival ( p = 0.665 and p = 0.052) compared with untreated controls. These findings, and our novel models, have potential implications for enhancing the clinical benefit of NK therapy in patients with advanced OC.